INFORMATION VALUE - Mircea, Gheorghita (Economics of Agriculture, 2012)
The paper intends to discuss the problem related to the knowledge transfer costs from the perspective of the economic actors as potential beneficiaries of this process. The approach uses the model for determining an optimal offer in uncertain circumstances related to the selling price and emphasizes the information value that a manger acquires in order to ease the decisional process regarding the offer level. In this context, the information value represents the total amount that the manager is willing to pay in order to get the perfect information regarding the output selling price, as a result of the difference between two levels of the average wealth utility (with and without knowledge transfer).